Exploring cytokine levels in pregnancy, preeclampsia, and sepsis-complicated preeclampsia - Mira Kusuma Wardhani; Harry Kurniawan Gondo (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2024)
Around the world, preeclampsia (PE) influences five to eight percent of pregnancies and contributes significantly to maternal mortality. This study applies a scientific observational cross-sectional review to examine how TNF-α, TNF-R1, and TNF-R2 play their roles in normal pregnancy, preeclampsia, and preeclampsia associated with sepsis. Blood tests were gathered from subjects at a local medical clinic in Malang, Indonesia, and TNF-α, TNF-R1, and TNF-R2 levels were surveyed utilizing the Enzyme-linked Immunosorbent Assay (ELISA) strategy. The results demonstrate raised TNF-α levels in both preeclampsia and preeclampsia with sepsis, along with expanded TNF-R1 and TNF-R2 receptor levels, signifying their association in these circumstances. Validation through bigger scope studies is basic, possibly situating TNF-α as an early indicative biomarker for sepsis. This study highlights the importance of TNF-α in pregnant mothers with preeclampsia and preeclampsia muddled by sepsis, uncovering possible analytic and remedial avenues.